2020
DOI: 10.3389/fmicb.2020.01479
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Enhance Biofilm Formation by Promoting Extracellular DNA Release Through sigB Upregulation in Staphylococcus aureus

Abstract: Bacterial biofilms do serious harm to the diabetic foot ulcer (DFU) because they play a crucial role in infection invasion and spread. Staphylococcus aureus , the predominant Gram-positive bacteria in diabetic foot infection (DFI), is often associated with colonization and biofilm formation. Through biofilm formation tests in vitro , we observed that S. aureus bacteria isolated from DFU wounds were more prone to form biofilms than those from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In a long-term study conducted between 2008 and 2015, Escherichia coli and Staphylococcus aureus were the two most common bacteria found to infect diabetic wounds (Zubair and Ahmad, 2019). This is supported by more recent findings in where biofilms of S. aureus have been found to be promoted by AGEs, which are increased in diabetic patients (Xie et al, 2020).…”
Section: Antibioticsmentioning
confidence: 72%
“…In a long-term study conducted between 2008 and 2015, Escherichia coli and Staphylococcus aureus were the two most common bacteria found to infect diabetic wounds (Zubair and Ahmad, 2019). This is supported by more recent findings in where biofilms of S. aureus have been found to be promoted by AGEs, which are increased in diabetic patients (Xie et al, 2020).…”
Section: Antibioticsmentioning
confidence: 72%
“…This discrepancy suggests that AGE-induced biofilm formation may be ica- independent, which would explain the lack of efficacy. We have observed a significant increase in extracellular DNA released by S. aureus in response to glucose-keratin exposure (data pending publication), and it has been independently reported that S. aureus eDNA release regulators are promoted by AGE exposure [ 17 ]. Thus, the eDNA dominant biofilm phenotype may be more resistant to ascorbic acid.…”
Section: Discussionmentioning
confidence: 96%
“…It is speculated that the accumulation of AGEs in the epidermis may play a role both in the etiology of disorders such as AD and dysbiosis of the skin microbiome. It has been reported that glycated proteins enhance S. aureus biofilm formation [ 17 , 18 ], which may increase its potential for pathogenicity. Biofilm confers antibiotic resistance [ 19 ], protects resident bacteria from host immune responses such as phagocytosis [ 20 ], and perpetuates the dominance of S. aureus on AD skin [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…DFI is a severe, common, and costly complication of diabetes, featured by wound healing and infection clearance disorders. As the most common Gram‐positive Cocci in DFI, S. aureus infection and biofilm formation 20 are frequently found in diabetic chronic foot wounds with poor patients outcomes. However, the exact reasons for the prolonged infection of S. aureus of DFI are still unclear 21,22 .…”
Section: Discussionmentioning
confidence: 99%